Do test design and uses influence test preparation? Testing a model of washback with Structural Equation Modeling. (January 2013) - Xie, Qin; Andrews, Stephen
This study introduces Expectancy-value motivation theory to explain the paths of influences from perceptions of test design and uses to test preparation as a special case of washback on learning. Based on this theory, two conceptual models were proposed and tested via Structural Equation Modeling. Data collection involved over 870 test takers of College English Test Band 4 in China. A perception of assessment questionnaire was given at the beginning of a 10-week preparation period; a test preparation questionnaire was given eight weeks later. Test takers who endorsed high-stakes, instrumental test uses as the primary purpose for taking the test tended to value test taking; test takers who perceived test design positively tended to attach high importance to test taking and appeared more confident. Furthermore, higher endorsed task value and higher expectation of test success jointly contributed to greater engagement in test preparation. Knowledge of the test was also related to increased self-regulation in test preparation and more practice of test-taking skills.